Screening for inhibitor tolerant Saccharomyces cerevisiae strains from diverse environments for use as platform strains for production of fuels and chemicals from biomass. (September 2018) - Mertens, Jeffrey A.; Kelly, Amy; Hector, Ronald E.
Abstract: Three Saccharomyces cerevisiae strains, YB-2625, Y-7567, and Y-1649, from a screen of over 160 strains, were selected based on tolerance to specific biomass hydrolysate inhibitors and subject to in depth analysis using varying concentrations of inhibitors and acid hydrolyzed corn stover. Growth assays with individual inhibitors demonstrated that detoxification of HMF and furfural have different impacts; detoxification of high concentrations of HMF results in a large increase in acetate production that is not present in the detoxification of furfural. Strains YB-2625 and Y-7567, demonstrated a reduced lag phase and higher growth in fermentations using corn stover hydrolysate relative to a previously isolated inhibitor tolerant strain. Genome sequencing of the two strains showed that both strains have some genes associated with inhibitor tolerance, but do not have the full complement of inhibitor associated genes, suggesting additional genes or genetic background may also play a role in increased inhibitor tolerance. Highlights: Screen performed to identify biomass hydrolysate inhibitor tolerant yeast strains. Two strains, of over 160 Saccharomyces sp. screened, with higher inhibitor tolerance. Detoxification of HMF, but not furfural, leads to greater acetate production. Genome sequence shows presence of some genes associated with inhibitor tolerance.